Performances of an Artificial Reagent for the One-stage Factor IX Assay - Meunier, L; Allain, J. P; Frommel, D (Thrombosis and Haemostasis, 1975)
A mixture of adsorbed normal human plasma and chicken plasma was prepared as reagent for factor IX measurement using a one-stage method. The substrate was found to be specific for factor IX. Its performances tested on samples displaying factor IX activity ranging from <l%–2,500% compared favorably with those obtained when using the plasma of severe haemophilia B patients as substrate.